If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -6(x + -5) = 2(x + 5) + 5(x + -4) Reorder the terms: 5x + -6(-5 + x) = 2(x + 5) + 5(x + -4) 5x + (-5 * -6 + x * -6) = 2(x + 5) + 5(x + -4) 5x + (30 + -6x) = 2(x + 5) + 5(x + -4) Reorder the terms: 30 + 5x + -6x = 2(x + 5) + 5(x + -4) Combine like terms: 5x + -6x = -1x 30 + -1x = 2(x + 5) + 5(x + -4) Reorder the terms: 30 + -1x = 2(5 + x) + 5(x + -4) 30 + -1x = (5 * 2 + x * 2) + 5(x + -4) 30 + -1x = (10 + 2x) + 5(x + -4) Reorder the terms: 30 + -1x = 10 + 2x + 5(-4 + x) 30 + -1x = 10 + 2x + (-4 * 5 + x * 5) 30 + -1x = 10 + 2x + (-20 + 5x) Reorder the terms: 30 + -1x = 10 + -20 + 2x + 5x Combine like terms: 10 + -20 = -10 30 + -1x = -10 + 2x + 5x Combine like terms: 2x + 5x = 7x 30 + -1x = -10 + 7x Solving 30 + -1x = -10 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 30 + -1x + -7x = -10 + 7x + -7x Combine like terms: -1x + -7x = -8x 30 + -8x = -10 + 7x + -7x Combine like terms: 7x + -7x = 0 30 + -8x = -10 + 0 30 + -8x = -10 Add '-30' to each side of the equation. 30 + -30 + -8x = -10 + -30 Combine like terms: 30 + -30 = 0 0 + -8x = -10 + -30 -8x = -10 + -30 Combine like terms: -10 + -30 = -40 -8x = -40 Divide each side by '-8'. x = 5 Simplifying x = 5
| -5x^3+6x^2= | | 5x^2-21x+19=1 | | -6n-12n=16 | | C(x)=18000+100x | | 3x+13+4x-8=180 | | R=(15.00-0.25*15.00)(0.12) | | sin(x)+sqrt(2)=-sin | | C(x)=1800+100x | | (3x^3+7x^2-11)+(5x^3+5x^2-8)= | | -0.666667x+0.333333+x=0.4 | | 5x-4(x-8)=2+2x | | 8i+14i-12i-21= | | P^2+2p=0.31 | | 5r^2-20r+20= | | 4+2n=29 | | 12*1/2= | | 1/2*3*4= | | 53.92x3.12= | | x+(x*.22)=x | | 3z+12=4+z | | 9/10-(-1/3)= | | 56u^2-15u+1= | | -18+x-1=16-15+2 | | 15vu-6v-10u+4= | | 3(z+4)= | | 6/8-sqrt5 | | 4x-15+3x+12=180 | | 6+2s-1=9s+17-4s | | 1/4x-5/8x=10-37 | | X^2+2x=-0.5 | | 8u^2+55u-7= | | 10x^2-13x-17=-8 |